CODE, COMMAND, AND CONSEQUENCES: WHO IS RESPONSIBLE FOR WAR CRIMES COMMITTED BY LETHAL AUTONOMOUS WEAPON SYSTEMS (LAWS)? - Samakashvili, Ana (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the study is to explore the legal and ethical challenges that arise in contemporary armed conflict due to the increasing integration of Lethal Autonomous Weapon Systems (LAWS). As these technologies gain operational relevance, the study seeks to examine who bears liability when autonomous systems perform actions that violate International Humanitarian Law (IHL). It also aims to assess whether existing legal instruments are adequate to address the complexities introduced by the autonomous decision-making capabilities of AI-driven lethal systems. Research methods: in the article, the research was conducted by using comparative-legal and doctrinal methods to evaluate how different legal systems and international actors respond to the challenge of regulating LAWS. The historical method was applied to trace the development of legal norms related to weapons technologies and armed conflict, providing context for understanding contemporary legal gaps and the need for updated regulation, and normative method was also used to emphasize the necessity of introduction new regulative and prohibitive norms to regulate the problem. Results: this study examines the legal and ethical challenges posed by LAWS in contemporary warfare. It highlights the difficulties in assigning liability when LAWS commit actions that violate International Humanitarian Law (IHL). The research also assesses the inadequacy of current legal frameworks in addressing these challenges and the need for new regulations to ensure accountability and the protection of civilians. Discussion: LAWS are capable of identify and shoot targets independently, without any human control, from one perspective, offer tactical advantages, such as speed, precision, and reduced direct involvement of human being, but on the other hand, it leads to a deeply unsettling legal and ethical dilemma: Who should be held responsible when an autonomous weapon system commits a war crime? Existing laws, rooted in the premise of human decision-making, are not easily applicable when a machine executes a potentially unlawful act without a clear human command. The legal enigma is who (or what) has responsibility in such scenarios threatens to undermine individual criminal responsibility and the protection of civilians during armed conflict.